Adult Cancer Patients’ Quality of Life After Outpatient Chemotherapy with JKN Coverage - Nancy Nancy; Tutik Maysaroh; Hubertus Genias Unggulian (Jurnal Jaminan Kesehatan Nasional, 2023)
Adult cancer patients who received chemotherapy with JKN coverage were enrolled on this observational cross-sectional study to evaluate their quality of life (QOL) and to identify the associated variables that affected QOL. Eligible patients who received outpatient chemotherapy at Keluarga Sehat Hospital were asked to complete an EORTC QLQ-C30 questionnaire, as well as a socio-demographic inquiry. We collected answers from 53 patients and converted them into EORTC dimensions and symptoms. One-way analysis of variance was used in addition to descriptive statistics and independent t-tests. The QOL average score was 78.93 ± 20.89, with a 95% CI (73.31-84.55). The highest performance was on the cognitive scale (94.03 ± 16.85), while the poorest was on the role scale (73.27 ± 27.91). Pain (95% CI [24.05, 36.95]) and fatigue (95% CI [23.14, 35.98]) were the most troubling symptoms reported. The marital status (p < 0.05) and cancer treatment history (p < 0.01) were factors affecting our population’s QOL. Through the understanding of the relationship between QOL and socio-demographic and medical variables, oncologists, chemotherapy providers, and health insurers can improve the quality of life of vulnerable populations.